Bacterial Diversity in the Digestive Tracts of Four Indian Air-Breathing Fish Species Investigated by PCR Based Denaturing Gradient Gel Electrophoresis - He,Suxu (2016)
ABSTRACT An investigation was conducted to identify the allochthonous microbiota (entire intestine) and the autochthonous microbiota in proximal intestine (PI) and distal intestine (DI) of four species of Indian air-breathing fish (climbing perch; Anabas testudineus, murrel; Channa punctatus, walking catfish; Clarias batrachus and stinging catfish; Heteropneustes fossilis) by PCR based denaturing gradient gel electrophoresis (DGGE). High similarities of the allochthonous microbiota were observed between climbing perch and murrel, walking catfish and stinging catfish, indicating similar food behavior. The autochthonous microbiota of PI and DI from climbing perch and murrel revealed more similarity, than the result obtained from walking catfish and stinging catfish. The autochthonous microbiota of climbing perch and murrel were similar with regard to the allochthonous microbiota, but no such similarity was observed in case of walking catfish and stinging catfish. The fish genotype and intestinal bacteria are well matched and show co-evolutionary relationship. Three fish species has its unique bacteria; autochthonous Enterobacter cloacae, Edwardsiella tarda and Sphingobium sp. in DI of climbing perch, Pseudomonas sp.; allochthonous and autochthonous in PI of walking catfish and uncultured bacterium (EU697160.1), uncultured bacterium (JF018065.1) and uncultured bacterium (EU697160.1) for stinging catfish. In murrel, no unique bacteria were detected.